The influence of different feed additives in broiler diets on productivity and meat yield - Tokić Vesna; Lazarević Miodrag; Sinovec Zlatan; Baltić Milan Ž.; Jokić Živan (Veterinarski Glasnik, 2007)
The objective of these investigations was to examine the influence of prebiotics based on mannan-oligosaccharides and polysaccharide complexes of micro elements (Fe, Cu, Zn, Mn) on production results and abattoir parameters for broilers of the hybrid Arbor Acres. The experiment was performed on 186 chicken divided into three equal groups, it lasted 42 days and was divided into 3 phases. The first phase lasted 21 days, the second 14, and the third seven days. The complete mix for initial fattening of broilers was used from days 1-21, and complete fodder mixes for closing fattening from days 21-35, and on days 35-42 of the experiment. Feeding was ad libitum and the broilers were maintained in a floor system. Broilers fed mixes of standard raw material composition and the usual nutritive values achieved an average daily growth of 49.10 g at an average daily feed consumption of 115.55 g and with food conversion of 2.35, while the yield was 71.90%. The addition of prebiotics based on mannan-oligosaccharides resulted in an increased average daily growth by 14.95% with a lower feed consumption by 2.67% and better conversion by 15.32%, while the yield was approximately the same as in the control group. The use of mixes to which polysaccharide complexes of micro elements have been added (Fe, Cu, Zn, Mn) resulted in a higher daily growth by 11.43%, with a lower feed consumption by 4.28% and better conversion by 14%. The yield was approximately the same in this group as in the controls. The results realized in these investigations, throughout the experimental period, indicate that the use of the examined additives significantly affected the growth and body mass of chicks and that it is nutritionally and economically justified.